The Efficacy and Safety of Mirabegron for the Treatment of Neurogenic Lower Urinary Tract Dysfunction: A Systematic Review and Meta-analysis - Zhang, Dongxu; Sun, Fengze; Yao, Huibao; Bao, Xingjun; Wang, Di; Cui, Yuanshan; Wu, Jitao (Frontiers in Pharmacology, 2021)
Abstract Background and objective: Over the last few years, mirabegron has been increasingly used as a therapeutic option for neurogenic lower urinary tract dysfunction. Here, we carried out a meta-analysis to investigate the efficacy and safety of mirabegron for the treatment of neurogenic lower urinary tract dysfunction. Methods: We used a range of databases to retrieve randomized controlled trials (RCTs) relating to mirabegron in patients with neurogenic lower urinary tract dysfunction, including PubMed, Embase, and Cochrane Library databases; our strategy conformed to the PICOS strategy. Results: Our analyses involved four RCTs involving 245 patients. We found that mirabegron treatment resulted in a significant improvement in bladder compliance [mean difference (MD) = 19.53, 95% confidence interval (CI): 14.19 to 24.87, P < 0.00001], urinary incontinence episodes (MD = -0.78, 95% CI: -0.89 to -0.67, P < 0.00001) and Incontinence-Quality of Life (I-QOL) (MD = 8.02, 95% CI: 3.20 to 12.84, P = 0.001). Significant differences were detected in terms of Patient Perception of Bladder Condition (PPBC) (MD = -0.54, 95% CI: -1.46 to 0.39, P = 0.26) and urinary urgency episodes (MD = -0.72, 95% CI: -3.1 to 1.66, P = 0.55). With regards to safety, there were no significant differences between mirabegron and control groups with regards to the incidence of drug-related adverse events [odds ratio (OR): 0.83, 95% CI: 0.43 to 1.59, P=0.57], arrhythmias (OR: 1.27, 95% CI: 0.37 to 4.38, P=0.70), hypertension (OR: 0.70, 95% CI: 0.13 to 3.82, P=0.68), or post-voiding residual volume (MD: 1.62, 95% CI: –9.00 to 12.24, P=0.77). Conclusion: Mirabegron is an efficacious and safe treatment for patients with neurogenic lower urinary tract dysfunction.